Pengaruh Lama Fermentasi terhadap Kandungan Bahan Ekstrak Tanpa Nitrogen Total Digestible Nutrient dan Gross Energy Tepung Kulit Singkong: The Effect of Fermentation Time on the Content of Extracts Nitrogen Free Energy, Total Digestible Nutrients and Gross Energy of Cassava Peel Flour - Godilifa Mersy Lopis; Gusti Ayu Yudiwati Lestari; Imanuel Benu (Universitas Nusa Cendana, 2023)
The purpose of this study was to find out the content of Extract Materials Nitrogen Free Energy, Total Digestible Nutrients and Gross Energy the effect of the length of time for fermentation of cassava peels. The method used for this research is the experimental method, through an experimental design using a Completely Randomized Design through 4 treatments, 3 replications to obtain 12 experimental elements. The treatments tested were KS0 = no fermentation, KS7 = 7 days of fermentation, KS14 = 14 days of fermentation and KS21 = 21 days of fermentation. The variables measured were the content of the Nitrogen-Free Energy, Total Digestible Nutrient and Gross Energy. The results of statistical tests showed that fermenting cassava peel flour at different lengths of time increased the Nitrogen-Free Energy and Total Digestible Nutrient, but did not increase the Gross Energy content. It can be concluded that the fermentation time of cassava peel flour using Effective Microorganism 4 was able to increase the content of the Nitrogen-Free Energy and Total Digestible Nutrient in the 7-day fermentation treatment, but the Gross Energy content was relatively the same. The best time needed to ferment cassava peel flour is 7 days. Tujuan dari penelitian ini agar dapat diketahui kandungan Bahan Ekstrak Tanpa Nitrogen, Total Digestible Nutrient dan Gross Energy pengaruh lama waktu fermentasi kulit singkong. Metode yang dipakai untuk penelitian ini yaitu metode eksperimen, melalui desain percobaan memakai Rancangan Acak Lengkap lewat 4 perlakuan, 3 ulangan sampai diperoleh 12 elemen percobaan. Perlakuan yang dicobakan adalah KS0 = tanpa fermentasi, KS7 = waktu fermentasi 7 hari, KS14 = waktu fermentasi 14 hari dan KS21 = waktu fermentasi 21 hari. Variable yang diukur adalah kandungan Bahan Ekstrak Tanpa Nitrogen, Total Digestible Nutrient dan Gross Energy. Hasil uji statistik memperlihatkan bahwa fermentasi tepung kulit singkong pada lama waktu yang berbeda meningkatkan Bahan Ekstrak Tanpa Nitrogen dan Total Digestible Nutrient, tetatpi tidak meningkatkan kandungan Gross Energy. Dapat disimpulkan bahwa lama waktu fermentasi tepung kulit singkong menggunakan Effective Microorganism 4 mampu meningkatkan kandungan Bahan Ekstrak Tanpa Nitrogen dan Total Digestible Nutrient pada perlakuan lama fermentasi 7 hari, namun terhadap kandungan Gross Energy relatif sama. Lama waktu terbaik yang dibutuhkan untuk fermentasi tepung kulit singkong adalah 7 hari.